Forms of enterprise personnel management - Li, Zi; Kobielieva, T. O.; Khodyrieva, O. O. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The report proves it. that effective human resource management helps to increase productivity, ensure employee satisfaction and achieve the company's strategic goals. We have created the most effective forms of personnel management for practical use in enterprises. These forms of personnel management can be used separately or combined depending on the needs and specifics of the enterprise. The main goal is to ensure effective personnel management to achieve the strategic goals of the organization.
Форми управління персоналом підприємства
Keywords: personnel management; results; motivation; production; efficiency; profit